A population-based study of the frequency and predictors of induced abortion among women with schizophrenia. (December 2019) - Brown, Hilary K.; Dennis, Cindy-Lee; Kurdyak, Paul; Vigod, Simone N.
Abstract : Background: Induced abortion is an indicator of access to, and quality of reproductive healthcare, but rates are relatively unknown in women with schizophrenia. Aims: We examined whether women with schizophrenia experience increased induced abortion compared with those without schizophrenia, and identified factors associated with induced abortion risk. Method: In a population-based, repeated cross-sectional study (2011–2013), we compared women with and without schizophrenia in Ontario, Canada on rates of induced abortions per 1000 women and per 1000 live births. We then followed a longitudinal cohort of women with schizophrenia aged 15–44 years ( n = 11 149) from 2011, using modified Poisson regression to identify risk factors for induced abortion. Results: Women with schizophrenia had higher abortion rates than those without schizophrenia in all years (15.5–17.5 v. 12.8–13.6 per 1000 women; largest rate ratio, 1.33; 95% CI 1.16–1.54). They also had higher abortion ratios (592–736 v. 321–341 per 1000 live births; largest rate ratio, 2.25; 95% CI 1.96–2.59). Younger age (<25 years; adjusted relative risk (aRR), 1.84; 95% CI 1.39–2.44), multiparity (aRR 2.17, 95% CI 1.66–2.83), comorbid non-psychotic mental illness (aRR 2.15, 95% CI 1.34–3.46) and substance misuse disorders (aRR 1.85, 95% CI 1.47–2.34) were associated with increased abortion risk. Conclusions: These results demonstrate vulnerability related to reproductive healthcare for women with schizophrenia. Evidence-based interventions to support optimal sexual health, particularly in young women, those with psychiatric and addiction comorbidity, and women who have already had a child, are warranted.